Nutrient Content and Microbial Quality of Soymilk-Carrot Powder Blend - Madukwe, E.U.; Eme, P.E.; Okpara, C.E. (Pakistan Journal of Nutrition, 2013)
This study evaluates the nutrient content and microbial quality of soymilk fortified with carrot powder. Carrots, soybeans, sugar and flavourings were bought from local retailers in Ogige main market, Nsukka in Enugu State, Nigeria. The fresh carrots were washed, scrapped, trimmed, sliced, sundried, grinded, packaged and stored in a labeled polythene bag. The soybean seeds were sorted, cleaned, washed, soaked for 18 hours, drained and blanched for 25 minutes at 89°C. The blanched beans were pulverized with hot water; the paste formed was diluted with water at 1:5 and then sieved to get the soymilk. The soymilk was cooked for 23 minutes at 87°C. Flavor agents and sugar were added, 20g each of carrot powder was added to 500ml and 600ml of soymilk respectively. Microbial loads of the samples were also determined. It revealed that proximate composition, vitamin and mineral contents of the fortified soymilk (CS2 and CS3) were higher than the plain soymilk (CS1). The total viable count of microbes of the samples CS1 and fortified soymilk (CS2 and CS3) were 4.85x10°CFU/mls, 6.25x101 CFU/mls and 6.80x101 CFU/mls, respectively. The result of the microbial counts revealed that the fortified soymilk (CS2 and CS3) contain higher microbial loads than the plain soymilk (CS1). Nutrition educators should encourage the public to use carrot powder-soymilk blend because of its source of micronutrient. Further researches should be done on the best way of reducing contamination in carrot powder.